Reconsidering the formation of dust void in axial magnetic field. Issue 4 (5th March 2022) - Wang, Yunfan; Sun, Pingyuan; Yu, Yongjun; Chen, Zhaoyang; Huang, Feng
Abstract: We propose a nonlinear fluid model to describe the dust void formation in a magnetic field environment. It is found that the radius of the dust void keeps decreasing as the intensity of the magnetic field increases. Further research shows that the circular motion of ions affects the balance of electric field force and ion‐drag force, which is the main reason for the change of dust voids. The Lorentz force of grains theoretically tends to increase the radius of the dust void, but the force is so small that it can be ignored.